Epizootic situation on helminths in cattle in the Republic of Udmurtia - M. E. Mkrtchyan; S. O. Movsesyan; I. A. Arkhipov (Российский паразитологический журнал, 2016)
Data on distribution of helminthosis and helminthocenosis structure in the Re- public of Udmurtia on the base of results of slaughter for 2001-2012 taking into account the parazitocenosis index calculation are provided. The analysis showed that the parasitic situation in the republic in recent years considerably has im- proved, but still most often trematodosis are detected at veterinary and sanitary ex- amination. The average degree of contamination of animals with fasciolosis is 13,48, with dicrocoeliosis - 2,39 %. Their total index in parazitocenosis fluctuates from 84,46 to 94,61 %. Data on structure of helminths fauna taking into account a share of each fellow member can be used further during the development and im- plementation of republican target programs for carrying out system of antiparasitic actions